Factors Associated with the Incidence of Hand Dermatitis Among Car and Motorcycle Wash Workers in East Padang District - Shafiqah Zawira; Gardenia Akhyar; Selfi Renita Rusjdi; Ennesta Asri; Biomechy Oktomalio Putri; Yustini Alioes (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2025)
Introduction: Hand dermatitis is a common occupational skin disorder caused by repeated exposure to irritants or allergens. Workers in car and motorcycle wash services are particularly vulnerable due to their frequent contact with detergents and cleaning agents, as well as prolonged exposure to wet work. This study aimed to identify factors associated with hand dermatitis among workers in East Padang District. Methods: A quantitative analytical observational study with a cross-sectional design was conducted among 32 workers selected through simple random sampling. Data were collected through direct interviews using a validated questionnaire. Univariate and bivariate analyses were performed, with chi-square tests used to evaluate associations between hand dermatitis and variables including working period, duration of contact, age, atopic history, personal hygiene, and use of personal protective equipment (PPE). Results: Hand dermatitis was identified in 65.6% of respondents. Bivariate analysis revealed significant associations between duration of contact (p = 0.020), personal hygiene (p = 0.027), and PPE use (p < 0.000) and the incidence of hand dermatitis. No significant associations were found for working period (p = 0.798), age (p = 0.211), or atopic history (p = 0.637). Discussion: Prolonged exposure to irritants, inadequate hygiene practices, and non-use of PPE likely heighten skin barrier disruption, predisposing workers to dermatitis. Conversely, factors such as age and atopic predisposition may play a minor role in this occupational group. Conclusion: Duration of contact, personal hygiene, and the use of PPE are significantly associated with hand dermatitis among car and motorcycle wash workers. In contrast, working period, age, and atopic history show no meaningful relationship. Strengthening preventive practices, remarkably consistent PPE use, is essential.